Flexural fatigue life prediction of CFRP-Nomex honeycomb sandwich beams - Rajaneesh, A. (2020)
Long-term flexural fatigue life of composite sandwich beams consisting of plain weave carbon 3K-70P/epoxy (CFRP) faceplates and Nomex honeycomb core is studied using time–temperature superposition principle (TTSP) by extending our previous study on laminates [Composites Part B: Engineering (19):539-547, 2016]. Considering negligible effect of temperature on the honeycomb core performance, time-temperature shift factors (TTSF) of the sandwich beams is assumed to be same as that of the CFRP faceplates. Hence, TTSFs are taken from previous laminates study. Constant strain rate (CSR) experiments at various temperatures and strain rates are conducted to construct the CSR master curve, followed by prediction and validation of creep strength master curve. Flexural fatigue tests were then conducted at various temperatures and load levels to construct S-N curves at respective temperatures. Finally, fatigue strength master curve is constructed. Within experimental scatter, predicted fatigue behavior at any given (a) frequency and (b) load ratio is confirmed to be in reasonable agreement with the experimental measurements.